SOSTDC1 downregulation in CD4+ T cells confers protection against obesity-induced insulin resistance - Dehai Li; Jing Zhu; Mingyue Zhang; Qiping Shi; Rong Guo; Daming Zhang; Pei Zheng; Hua Zhang; Guangqiang Li; Jie Wu; Guodong Sun; Qiong Wen; et al. (Cell Reports)
Summary: Adipose-resident T cells play a crucial role in the development of obesity-induced insulin resistance. However, the specific mechanisms, particularly those involving non-immune cytokines, remain unclear. Here, we report significantly elevated levels of sclerostin domain-containing protein 1 (SOSTDC1) in individuals with type 2 diabetes (T2D), showing positive correlations with fasting glucose and HbA1c. T cell-specific Sostdc1-deficient mice exhibit resistance to age-induced adipose lipid accumulation and glucose dysregulation at 12 months and protect against obesity-induced insulin resistance without affecting proinflammatory macrophage infiltration or adipose inflammation. Mechanistically, SOSTDC1 disrupts the lipid balance in adipocytes by promoting lipogenesis and inhibiting lipolysis through the LRP5/6-β-catenin pathway. Furthermore, T cell receptor (TCR) signaling significantly amplifies SOSTDC1 secretion in CD4+ T cells. In summary, our study uncovers an additional mechanism by which T cells contribute to obesity and insulin resistance, suggesting that inhibiting SOSTDC1 could be a promising immunotherapeutic strategy for metabolic disorders.